CHANGES IN MEANING OF WORK COMPONENTS IN FIRST EMPLOYMENT YEARS: A LONGITUDINAL ANALYSIS - Gracia, Francisco Javier; Martín, Pilar; Rodríguez, Isabel; Peiró, José María (Anales de Psicología / Annals of Psychology, 2001)
In this paper it is analysed the meaning of working evolution of young people in their beginning three years of employment through the study of its components. Sample was composed by 238 first-employment young people belonging to two different occupations (clerical workers and metal manufacturers). These young people were surveyed in three different moments along about three years. Results show that the different components of meaning of working vary differently through time. Results direction indicates that employment first experiences are afectting young people negatively. As a whole, results are a support to interaccionist thesis regarding to the controversial scientific community mantain about work meaning stability.